Analysis of neutralizing antibodies to COVID-19 inactivated or subunit recombinant vaccines in hospitalized patients with liver dysfunction - Li, Hu; Li, Shiyin; Xu, Pan; Wang, Xiaohao; Deng, Huan; Lei, Yu; Zhong, Shan (Frontiers in Immunology, 2023)
Background: The neutralizing antibodies (NAbs) response after COVID-19 vaccination after liver dysfunction is unclear. In this study, we evaluated the NAbs response after COVID-19 vaccination in hospitalized patients suffering from liver dysfunction. Methods: In this cross-sectional study with longitudinal follow-up, we enrolled eligible patients with liver dysfunction and healthy volunteers with full-course COVID-19 vaccination. Blood samples were collected for the NAbs testing at the time of admission and after treatment. Multiple regression analysis to assess independent risk factors affecting NAbs response. Results: A total of 137 patients and 134 healthy controls (HC) were enrolled. Both seropositivity (65.7% vs 80.6%, p<0.01) and titer (3.95 vs 4.94 log2 AU/ml, p<0.001) of NAbs in patients were significantly lower than that in HC. The decrease of antibody titer in patients was significantly faster than that in HC. After adjusting for potential confounding factors, males (odds ratio [OR]: 0.17; 95% confidence interval [CI]: 0.06, 0.46; p<0.001) and severe liver damage (OR: 0.30; 95% CI: 0.12, 0.71; p<0.01) were significantly associated with reduction of the probability of NAbs seropositivity in the multiple regression analysis. Males (β =-1.18; 95% CI: -1.73,-0.64) and chronic liver diseases (β =-1.45; 95% CI: -2.13, -0.76) were significantly associated with lower NAbs titers. In 26 patients with liver failure, both antibody seropositivity (53.8% vs 84.6%, p<0.05) and titer (3.55 vs 4.32 log2 AU/ml, p<0.001) did not decrease but increased after artificial liver plasmapheresis. Conclusions: NAbs response to COVID-19 inactivated or subunit recombinant vaccines was waning in patients with liver dysfunction. Moreover, patients with male sex, severe liver injury and chronic liver diseases have an increased risk of poor antibody responses.